Audit Sistem Informasi E-Learning Menggunakan Framework Cobit 2019 dengan Domain DSS - Firdaus, Muhammad Adam; Suyatna, Nano (Ma'soem University, 2025)
This study aims to audit the Learning Management System (LMS) system at Bhakti Kencana University Bandung using the COBIT 2019 framework with a focus on the Deliver, Service, and Support (DSS) domain. This research includes three main objectives: (1) Conducting an audit of the LMS system by utilizing COBIT 2019 in the DSS domain, (2) Evaluating the maturity, security, and convenience level of the LMS system, and (3) Providing recommendations and suggestions for future system management improvements. The method used is quantitative with an analysis of the implementation and effectiveness of the system. The audit results showed that the LMS system's achievement value was at level 4, namely Managed and Measurable, which indicates that the institution has a clear process and all teams understand how the process works. The conclusion of this study is that the quality of support service request management at Bhakti Kencana University Bandung has met the standards measured in the COBIT 2019 framework, especially in the analysis of DSS1 (Managing Service and Support Requests), DSS2 (Managing Infrastructure and Platform), and DSS3 (Managing Information Security and Data Privacy). The service and support of the e-learning system are rated very good